Infection with cytomegalovirus is not associated with premature mortality - Stuart P. Adler; Al M. Best; Beth Marshall; George W. Vetrovec (MDPI AG, 2011)
Over 90% of the world's population acquires a cytomegalovirus (CMV) infection. This infection, although asymptomatic or self-limiting, is a major burden to the immune system. For this reason, and because CMV immunization is possible, determining whether CMV can cause reduced longevity, particularly among those with coronary artery disease, is important and previous reports have been conflicting. Thus our objective was to assess the association between CMV infection as defined serologically and antibody levels against CMV and longterm survival (18 years). We completed a prospective observational cohort study of 915 consecutive patients (mean age 58 years) undergoing coronary angiography. CMV immunoglobulin levels were measured at baseline using either a whole cell CMV antigen or a purified protein antigen (gB). After adjustment for potentially confounding variables (age, race, gender, body mass index, the presence or absence of coronary artery disease, the number of diseased vessels, diabetes, renal disease, hypertension, dialysis, congestive heart failure, and the maximum percent reduction in luminal diameter), Cox's proportional hazards models showed no association between CMV seropositivity or levels of antibodies against CMV by either assay and longevity for both patients with or without coronary artery disease (CAD) nor for those under or over 70 years of age at baseline. Our observations suggest that universal immunization against CMV may not improve longevity.